2023
DOI: 10.1021/acs.jafc.3c00678
|View full text |Cite
|
Sign up to set email alerts
|

Critical Sites of Serine Acetyltransferase in Lathyrus sativus L. Affecting Its Enzymatic Activities

Abstract: LsSAT2 (serine acetyltransferase in Lathyrus sativus) is the rate-limiting enzyme in biosynthesis of β-N-oxalyl-l-α,β-diaminopropionic acid (β-ODAP), a neuroactive metabolite distributed widely in several plant species including Panax notoginseng, Panax ginseng, and L. sativus. The enzymatic activity of LsSAT2 is post-translationally regulated by its involvement in the cysteine regulatory complex in mitochondria via interaction with β-CAS (β-cyanoalanine synthase). In this study, the binding sites of LsSAT2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous research has shown that the highly conserved β1c–β2c loop, which we defined as the β7–β8 loop, plays a key role in the binding of SAT proteins to serine (Yi et al 2013 ). In addition, the ten residues of the C-terminus of SAT are used to combine the active site of OASTL and form the cysteine synthase complex (Bogdanova and Hell 1997 ; Jez and Dey 2013 ; Ma et al 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the highly conserved β1c–β2c loop, which we defined as the β7–β8 loop, plays a key role in the binding of SAT proteins to serine (Yi et al 2013 ). In addition, the ten residues of the C-terminus of SAT are used to combine the active site of OASTL and form the cysteine synthase complex (Bogdanova and Hell 1997 ; Jez and Dey 2013 ; Ma et al 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%